Effect of Benomyl on Chitinase and β-1,3-Glucanase Production by Free and Alginate Encapsulated Trichoderma harzianum - Mohammed S. El-Katatny; Gehan M. Shaban; Ahmed M. A. Hetta; Momein H. El-Katatny; Hesham M. El-Komy (Food Technology and Biotechnology, 2004)
On PDA-benomyl plates growth of Trichoderma harzianum was inhibited by 20 and 30 % at benomyl 1 and 2 μg/mL, respectively, and was completely inhibited at 5 μg/mL. In minimal synthetic medium (MSM) amended with different concentrations of benomyl (1.0, 3.0, 5.0, 7.0 and 10.0 μg/mL), fungal immobilisation improved chitinase and β-1,3-glucanase production at low benomyl concentrations (1, 3 and 5 μg/mL). Further increase in the production of both enzymes was obtained by immobilisation at higher benomyl concentrations (7 and 10 μg/mL). Fungal immobilisation increased bound chitinase by 15- to 30-fold at 3 and 5 μg/mL benomyl concentration, respectively. However, no effect was obtained on the bound β-1,3-glucanase. Different benomyl concentrations (0.3 to 1500 μg/mL) had no significant inhibitory effect on the activities of free or immobilised chitinase and β-1,3-glucanase. It could be suggested that either immobilised Trichoderma or immobilised chitinase and β-1,3-glucanase could be used in combination with benomyl to control plant pathogens.